PELATIHAN DAN PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN DAN ADMINISTRASI PERPAJAKAN PADA INDUSTRI TAHU TEMPE DI DESA SUMBER HARUM - Sahrir, Sahrir; Zahran, Izal; Sari, Nispa (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this service is to carry out training and assistance in the preparation of financial and tax reports in the tofu and tempeh industry in Sumber Harum Village. Based on the results of observations and FGDs, two problems were encountered: 1) Do not have an application/financial reporting system, 2) Do not understand the preparation of tax administration so it is difficult to fulfill business tax obligations. Based on these problems, two types of activities were carried out, namely: First, mentoring and training in the preparation of financial reports, this stage of activity started with the provision of basic accounting materials, followed by making financial report applications using Microsoft Excel and training on the use of applications that had been made. Second, training and assistance in the preparation of tax administration, this activity begins with the provision of basic taxation materials such as tax rights and obligations, procedures for calculating PPh 21 and final PPh, making ebilling, and reporting SPT through efilling. In general, the implementation of this service has a positive impact on 3 important aspects, 1) Business actors already have knowledge of basic accounting and already have financial statement applications. With this application, it will be easier for industry owners to compile their financial reports so that they can control their businesses at any time. 2) Business actors already know their business tax rights and obligations, so it is hoped that MSMEs, as support the nation's economy, can play a role in increasing tax revenue. 3) Make it easier to plan future businesses, because they already have a good bookkeeping system that can provide comprehensive information.